The suspension characteristics data obtaining techniques based on image processing - Антоненков, Дмитрий Александрович (Eastern-European Journal of Enterprise Technologies, 2014)
At present, special attention is paid to creating new technical means and information technologies for the aquatic environment control. Technical means for obtaining information about the parameters of suspended matters in seawater were discussed in the paper. The developed method, allowing simultaneously obtain data on the concentration and size composition of suspended matters in seawater using image processing of environment was described. Using electro-optical converter as an electronic shutter allows to obtain the necessary exposure time to register the processes with high temporal variability. The description of the working procedure of the developed specialized stand, designed for laboratory testing and calibration of technical means, used for determining the suspension characteristics was given. Using the special bottom material resuspension technology has allowed to obtain the conditions for the experiments that are close to reality in terms of the bottom material suspension process dynamics. The data the on size composition and concentration of the suspension, obtained during laboratory testing of the designed technical means were given. The studies allow to create the technical means that are able to rapidly determine the parameters of water-suspended matters of bottom sediments in natural conditions. The developed specialized test stand allows to perform adjustment and calibration of various instruments, used to determine the parameters of suspended matters, in particular suspension traps, directed light attenuation coefficient meters (turbidimeters), hydroacoustic suspension geometry tools (meters of vertical distribution of the suspension concentration).